2010
DOI: 10.2337/dc10-1213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on Survival After Amputation in Individuals With Diabetes

Abstract: OBJECTIVETo identify factors that influence survival after diabetes-related amputations.RESEARCH DESIGN AND METHODSWe abstracted medical records of 1,043 hospitalized subjects with diabetes and a lower-extremity amputation from 1 January to 31 December 1993 in six metropolitan statistical areas in south Texas. We identified mortality in the 10-year period after amputation from death certificate data. Diabetes was verified using World Health Organization criteria. Amputations were identified by ICD-9-CM codes 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 23 publications
9
133
3
3
Order By: Relevance
“…7 This finding is in agreement with previous studies that have also explained the devastating effects of renal disease. Previous studies report that BKA patients face a 77%-86% 1-year survival rate, a 28%-58% 5-year survival rate, and a 35% 10-year survival rate.…”
Section: Clinical Relevancesupporting
confidence: 83%
See 1 more Smart Citation
“…7 This finding is in agreement with previous studies that have also explained the devastating effects of renal disease. Previous studies report that BKA patients face a 77%-86% 1-year survival rate, a 28%-58% 5-year survival rate, and a 35% 10-year survival rate.…”
Section: Clinical Relevancesupporting
confidence: 83%
“…Unfortunately, all studies describing survival rates following a BKA are confounded by the inconsistent timing of the amputation and the comorbid conditions inherent to this population. [1][2][3][4][5][6][7][8] No study to date has demonstrated a BKA to be an independent variable that decreases survival.…”
Section: Scopementioning
confidence: 99%
“…Improper prevention of diabetic foot conditions can result in significant morbidity, decreased function and quality of life (9). If the condition is severe enough, the pathology involved may require radical surgical management in the form of amputations (10,11) and can be life threatening (12,13). Proper foot care is an essential component in both the prevention and management of diabetic foot disease.…”
Section: Introductionmentioning
confidence: 99%
“…La tasa de mortalidad a los cinco años posterior a una amputación mayor puede alcanzar hasta el 78% 14,20 , y la incidencia de una segunda amputación de la extremidad contralateral se aproxima a la mitad de los casos dentro de dos años siguientes 21 . Por lo anterior, se han realizado esfuerzos en mejorar las técnicas y consideraciones quirúrgicas, dado que es otra de las variables que pueden influir en los resultados, utilizando aquellas que se han asociado a mayores tasas de éxito, como las utilizadas en el estudio realizado por Kallio y colaboradores, con una muestra de 63 pacientes diabéticos con lesiones en pie y realizando un seguimiento a 1,5 y 10 años 22 , en el que se dio cobertura realizando transferencia de colgajos libres con una excelente tasa de supervivencia libre de amputación del 90% a largo plazo, siempre y cuando este indemne la arteria encargada del aporte vascular en dicha zona.…”
unclassified
“…Existen diversas publicaciones que sustentan la evidencia mostrada anteriormente, en los que se demuestra que el salvamento de la extremidad aumenta la supervivencia de la población diabética; así, un estudio retrospectivo publicado por Lavery y colaboradores utilizando técnicas avanzadas para la reconstrucción de tejidos blandos 20 , mostró que mediante la preservación de la extremidad en pacientes diabéticos, la supervivencia a los ocho años fue de 59%, pese a que pueden requerir mayor número de intervenciones y tiempo de cicatrización.…”
unclassified